Gaya Hidup Masyarakat Hedonisme di Kota Lhokseumawe - Ramadhan Razali; Fuadi (Jurnal EMT KITA, 2023)
Teenagers have obligations of education and achievement, and may even join organizations that help them meet their life needs. That's because when you're young, you're curious. As teenagers want to try many new things that define the lifestyle of teenagers. The purpose of this study is to know and describe in detail the dynamics of hedonistic lifestyles in young women. The methods used are quantitative using targeted techniques to obtain complete information. It is an interactive method that is used as a method of collecting data through interviews and involves two-way communication. Research has shown that hedonistic lifestyles are those who see happiness and pleasure unilaterally and take advantage of this to seek expected pleasure. Activities such as shopping, traveling, watching movies, and hanging out at the mall are spent 3-6 hours a day, 2-3 times a week, at the mall with friends.